MRI features of primary cardiac lymphoma: case report and literature review - Xie, Dongmei; Li, Yudan; Tang, Chunyong; Zou, Qing (Frontiers in Oncology, 2025)
PurposeThis study aimed to further enhance the understanding of the imaging features of primary cardiac lymphoma (PCL), improve preoperative diagnostic accuracy, and reduce the misdiagnosis rates.MethodsThis study reports on a case of a 63-year-old man who presented with 3-day-long dizziness and bilateral lower limb edema. Initial transthoracic echocardiography detected a 4.5-cm × 5-cm mass without blood flow in the right atrium, suspected as a thrombus or tumor. Subsequently, cardiac MRI (3.0T Ingenia, Philips, Best Netherlands) was performed. Pre-contrast black blood turbo spin echo (TSE) T1-weighted imaging (T1WI), T2-weighted imaging (T2WI), T2 fat saturation (STIR), and retrospective ECG-triggered balanced turbo field echo (steady-state free precession) sequences on short and long axes were used.ResultsMRI showed a roundish solid mass in the right atrium with clear margins, broad-based attachment to the anterior/posterior walls, adjacent right atrial wall thickening, inferior vena cava inlet narrowing, and protrusion into the tricuspid orifice during atrial systole. First-pass perfusion presented homogeneous progressive enhancement, while the delayed phase showed patchy irregular enhancement. Due to limited knowledge about PCL, a preliminary diagnosis of cardiac myxoma was made. Eventually, tumor resection was carried out, and postoperative pathology confirmed it as right atrial diffuse large B-cell lymphoma (DLBCL) with a Ki-67 proliferation index of 90%. Although the symptoms improved post-surgery, the patient refused further chemotherapy and died shortly.ConclusionThis case highlights that MRI plays a significant role in the diagnosis of PCL, helping to identify characteristic imaging features and reduce misdiagnosis. Preoperative biopsy is crucial for accurate diagnosis, and chemotherapy is essential for improving patient survival. Further research is needed to better understand the imaging features of this rare tumor and optimize treatment strategies.